1992
DOI: 10.1099/0022-1317-73-7-1881
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two variants of Panolis flammea multiple nucleocapsid nuclear polyhedrosis virus

Abstract: The baculovirus Panolisflammea multiple nucleocapsid nuclear polyhedrosis virus (PfMNPV) was originally isolated from a natural virus epizootic and shown to consist of a mixture of variants. Two subclasses of variants (PfMNPV A and B) were identified by Southern blot hybridization, their polyhedrin genes being located on different restriction fragments. The proportion of the A and B variants changed according to the larval host in which the virus was propagated; PfMNPV(B) predominated in P. flammea but PfMNPV(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Most of the alterations within the genome are concentrated in one region (HindIII X/R fragments), although there are polymorphisms in two other areas. An earlier analysis of one of our variants (Pf7) also demonstrated changes in these three areas (Weitzman et al, 1992). Preliminary DNA sequencing of an enlarged HindIII R fragment (from Pf9) has shown that sequences corresponding to a chitinase gene are found within this region, with the closest match being to chitinases found in other NPVs (Paul, 1997).…”
Section: Discussionmentioning
confidence: 82%
“…Most of the alterations within the genome are concentrated in one region (HindIII X/R fragments), although there are polymorphisms in two other areas. An earlier analysis of one of our variants (Pf7) also demonstrated changes in these three areas (Weitzman et al, 1992). Preliminary DNA sequencing of an enlarged HindIII R fragment (from Pf9) has shown that sequences corresponding to a chitinase gene are found within this region, with the closest match being to chitinases found in other NPVs (Paul, 1997).…”
Section: Discussionmentioning
confidence: 82%
“…1). HindIII-F fragment variation was conWrmed by the presence of a larger fragment (F) and two smaller fragments (F 1 and F 2 ), as described by Weitzman et al (1992). Fig.…”
Section: Paxnpv Hindiii-f Fragmentmentioning
confidence: 99%
“…Hybridization analysis was carried out under high stringency conditions using [ -32 P]dATP labeled PaXNPV HindIII-R and -X fragments, using the method described by Sambrook et al (1989). Due to its high degree of sequence similarity, the MbMNPV polh was used to probe the PaXNPV HindIII-F fragments as described by Weitzman et al (1992). The probed membrane was exposed against a storage phosphor screen (Molecular Dynamics) and scanned using a phosphorimager (Typhoon 8600 Variable Mode Imager, Molecular Dynamics).…”
Section: Paxnpv Dna Puriwcation and Southern Hybridisationmentioning
confidence: 99%
See 2 more Smart Citations